"We were healers, witches, we were oracles.": Women’s Transformative Power in African Traditional Religions and African Initiated Churches - Frost, Marie-Luise (Interdisciplinary journal for religion and transformation in contemporary society, 2025)
African Initiated Churches are often seen as bridge-builders between African Traditional Religions and Christianity - as those who attracted a lot of followers because they maintained elements of traditional African beliefs that were dismissed by missionaries. This paper investigates the relationship between African Traditional Religions and African Initiated Churches focussing on its impact on the roles of women. It finds that both restricting and liberating aspects are taken over from African Traditional Religions to present-day African Initiated Churches. The religious traditions can affirm each other to foster the exclusion of women. Yet they also give room to spiritual power and charismatic authority that women may gain through age, status and divine or ancestral calling. These attributes enable women to fundamentally transform their own situation - e.g. from sick social misfits to powerful leaders - as well as to denounce and challenge existing power structures in the wider community.